A conceptual framework of web-based academic advisory information system - Ishak, Isma; Lehat, Mohd Lezam (Faculty Of Computer & Mathematical Sciences, 2012)
Web-based academic advising systems are gaining popularity among universities in recent times. Academicians are considering introducing these systems for their various benefits, even though only a few universities currently have a web-based advising system. Most web-based academic advising systems focus on student course planning. This research aims to determine the most important elements that should be considered in designing a web-based academic advisory system. A literature survey will be conducted to investigate current issues in developing web-based academic advising systems. Observations of existing web-based academic advisory systems in local and international educational institutions will also be undertaken to examine the elements included in these systems. Finally, questionnaires will be distributed to collect data regarding existing academic advisory systems. At the conclusion of the research, it is expected that a framework for a web-based academic advisory system will be developed. This framework will contribute to the development of best practices for web-based academic advisory systems.